The Role of Interactive Flat Panel (IFP) in Shaping Indonesia’s Digital Learning Policy: A Vision for Educational Reform in the Prabowo–Gibran Era - Usman Jayadi (Lafadz Jaya Publisher, 2025)
This study explores the role of Interactive Flat Panels (IFPs) as transformative digital learning media in shaping Indonesia’s educational reform under the Prabowo–Gibran administration (2024–2029). The research employs a descriptive qualitative approach, synthesizing scholarly literature and education policy analyses to conceptualize how IFP integration supports national digital education goals. Globally, IFPs have been proven to enhance student engagement, learning outcomes, and teacher performance through interactive, multimedia-based instruction. Within the Indonesian context, their adoption aligns with the Merdeka Belajar and Smart Schools Indonesia initiatives, which emphasize technological equity, digital sovereignty, and 21st-century learning competencies. The findings indicate that IFPs can foster interactive and collaborative learning environments, strengthen teachers’ digital competencies, and facilitate Education 5.0 implementation nationwide. However, several barriers persist, including infrastructure inequality, limited teacher readiness, and financial constraints in public schools. Addressing these challenges requires multi-sectoral collaboration, capacity-building programs, and localized production strategies to ensure sustainability and affordability. The study concludes that IFPs are not merely instructional technologies but strategic policy instruments driving Indonesia’s digital transformation in education. Their effective integration can bridge pedagogical and technological divides, positioning Indonesia as a leader in digital learning innovation across Southeast Asia.